Rowell’s syndrome – case report and review of the literature - Zofia A. Gerlicz-Kowalczuk; Joanna Krzysiek; Małgorzata Dominiak; Andrzej Kaszuba (Przegląd Dermatologiczny, 2016)
Introduction. Rowell’s syndrome is a rare subtype of subacute lupus erythematosus associated with erythema multiforme-like skin lesions, positive antinuclear antibodies and anti-Ro/La-antibodies. Objective . To present a case of Rowell’s syndrome. Case report . We describe a case of an 82-year-old man who presented with erythema multiforme-like eruption on the upper extremities and trunk and fulfilled the diagnostic criteria of Rowell,s syndrome. Conclusions . Patients with these characteristic clinical and immunological features of Rowell,s syndrome are rarely seen and reported in the literature. The discussion concerning the character of the disease is still ongoing.